The landscape of somatic mutations in infant MLL-rearranged acute lymphoblastic leukemias - Andersson, Anna K; Ma, Jing; Wang, Jianmin; Chen, Xiang; Gedman, Amanda Larson; Dang, Jinjun; Nakitandwe, Joy; Holmfeldt, Linda; Parker, Matthew; Easton, John; Huether, Robert; Kriwacki, Richard; et al. (Nature genetics, 2015)
Anna Andersson, Tanja Gruber, James Downing and colleagues report a genomic analysis of infant acute lymphoblastic leukemias with MLL rearrangements. They identify recurrent activating mutations in tyrosine kinase, phosphatidylinositol 3-kinase and RAS pathway genes but find that these mutations were often present in minor subclones and lost at the time of relapse. Infant acute lymphoblastic leukemia (ALL) with MLL rearrangements ( MLL -R) represents a distinct leukemia with a poor prognosis. To define its mutational landscape, we performed whole-genome, exome, RNA and targeted DNA sequencing on 65 infants (47 MLL -R and 18 non– MLL -R cases) and 20 older children ( MLL -R cases) with leukemia. Our data show that infant MLL -R ALL has one of the lowest frequencies of somatic mutations of any sequenced cancer, with the predominant leukemic clone carrying a mean of 1.3 non-silent mutations. Despite this paucity of mutations, we detected activating mutations in kinase-PI3K-RAS signaling pathway components in 47% of cases. Surprisingly, these mutations were often subclonal and were frequently lost at relapse. In contrast to infant cases, MLL -R leukemia in older children had more somatic mutations (mean of 6.5 mutations/case versus 1.3 mutations/case, P = 7.15 × 10 −5 ) and had frequent mutations (45%) in epigenetic regulators, a category of genes that, with the exception of MLL , was rarely mutated in infant MLL -R ALL.